Microsurgery of Brainstem Cavernoma: Challenges and Outcomes - Paudel, Kumar; Rai, Prahasan; Khadka, Namrata; Bhattarai, Sushil Mohan; Rajbhandari, Binod; Aryal, Sameer; Shrestha, Rajendra; Jha, Rajiv (Nepal Journal of Neuroscience, 2023)
Cavernous malformation of brainstem is at increased risk of hemorrhage compared to supratentorial cavernomas. Increased morbidity associated with brainstem cavernoma (BCs) is defined by the inherent eloquence of the surrounding structures. At present watchful waiting, microsurgical resection and gamma knife surgery are the treatment modalities for symptomatic brainstem cavernoma. However, in the resource limited settings microsurgical excision by selecting an appropriate corridor can help in gross total removal in the meantime improving the neurological deficit and patient satisfaction. In this case series we have reviewed cavernomas of midbrain and pons, the technical difficulty with its management and its outcomes.